2020
DOI: 10.3390/ijms21197168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mini-Dystrophin on Dystrophin-Deficient, Human Skeletal Muscle-Derived Cells

Abstract: Background: We are developing a novel therapy for Duchenne muscular dystrophy (DMD), involving the transplantation of autologous, skeletal muscle-derived stem cells that have been genetically corrected to express dystrophin. Dystrophin is normally expressed in activated satellite cells and in differentiated muscle fibres. However, in past preclinical validation studies, dystrophin transgenes have generally been driven by constitutive promoters that would be active at every stage of the myogenic differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(79 reference statements)
3
3
0
Order By: Relevance
“…Cell images were then used to extract the myotube area (MHC-positive area), and nuclei count (Figure 1C ), which was used to compute the fusion index (See Methods). As expected, the fusion index for the DMD donors (DMD #1 and DMD #4) was significantly lower compared to non-DMD donors (Non-DMD #1 and Non-DMD #3) (Meng et al, 2020 ).…”
Section: Characterizing Primary Donor Cells For Myoscreen Platformsupporting
confidence: 80%
“…Cell images were then used to extract the myotube area (MHC-positive area), and nuclei count (Figure 1C ), which was used to compute the fusion index (See Methods). As expected, the fusion index for the DMD donors (DMD #1 and DMD #4) was significantly lower compared to non-DMD donors (Non-DMD #1 and Non-DMD #3) (Meng et al, 2020 ).…”
Section: Characterizing Primary Donor Cells For Myoscreen Platformsupporting
confidence: 80%
“…Cell images were then used to extract the myotube area (MHC-positive area), and nuclei count (Figure 1C ), which was used to compute the fusion index (See Methods). As expected, the fusion index for the DMD donors (DMD #1 and DMD #4) was significantly lower compared to non-DMD donors (Non-DMD #1 and Non-DMD #3) (Meng et al, 2020 ).…”
Section: Characterizing Primary Donor Cells For Myoscreen Platformsupporting
confidence: 80%
“… 25 We have previously reported that expression of minidystrophin in DMD muscle stem cells can adversely affect their proliferation and myogenic differentiation in vitro. 26 Therefore, it would be advantageous to use a muscle-specific promoter that drives transgene expression only in differentiated myotubes/myofibers and is small enough to fit into the lentiviral vector together with the large full-length DMD human cDNA.…”
Section: Introductionmentioning
confidence: 99%